REACTIONS TO PEDRO FORTES - Prado, Mariana Mota; Trebilcock, Michael J. (REI - REVISTA ESTUDOS INSTITUCIONAIS, 2020)
In a very provocative piece, Pedro Fortes explores the idea of creating a charter city in Rio de Janeiro and raises the question of whether charter cities can be considered institutional bypasses. As he acknowledges, this is beyond the scope of our book: we did not explore rulemaking bypasses. Rather, the focus of our attention was on institutions that deliver services. The reason for limiting the scope of our analysis becomes clear in Fortes’ piece: through a series of comparative and historical analogues to charter cities, Fortes shows that this kind of reform raises significant challenges.